2014
DOI: 10.1186/1999-3110-55-27
|View full text |Cite
|
Sign up to set email alerts
|

Application of an inducible transposon with anther culture in generation of di-haploid homologous mutants

Abstract: BackgroundInsertional mutagenesis represents one of the most effective ways to acquire information about a plant gene’s function. However, it is hindered by the autosomal genome being diploid and therefore, most mutations being recessive. The problem is addressed by inducing the transposition during anther culture so that selected mutations can be transmitted and then regenerated to a homozygous state.ResultsTo this end, we treated transgenic rice floral tissues containing the inducible transposon with an indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…COKC was introduced into rice plants and activated by salicylic acid (SA) to trigger transposition events. The assumption was that transposition could be induced during anther culture, allowing selected mutations to be transmitted and recovered in the homozygous state in DH regenerated plants [381]. Yang and Charng [381] used five independent transgenic lines, each containing a single copy of COKC, as the plants from which anthers were taken for callus production and regeneration of DH plants.…”
Section: Monocot Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…COKC was introduced into rice plants and activated by salicylic acid (SA) to trigger transposition events. The assumption was that transposition could be induced during anther culture, allowing selected mutations to be transmitted and recovered in the homozygous state in DH regenerated plants [381]. Yang and Charng [381] used five independent transgenic lines, each containing a single copy of COKC, as the plants from which anthers were taken for callus production and regeneration of DH plants.…”
Section: Monocot Speciesmentioning
confidence: 99%
“…The assumption was that transposition could be induced during anther culture, allowing selected mutations to be transmitted and recovered in the homozygous state in DH regenerated plants [381]. Yang and Charng [381] used five independent transgenic lines, each containing a single copy of COKC, as the plants from which anthers were taken for callus production and regeneration of DH plants. The authors observed that inducible transposon was active during callus regeneration, resulting in around 5% of the mutants possessing transposon events in the homozygous condition.…”
Section: Monocot Speciesmentioning
confidence: 99%